2018
DOI: 10.1007/s00205-018-1218-4
|View full text |Cite
|
Sign up to set email alerts
|

Global Regularity of 2D Density Patches for Inhomogeneous Navier–Stokes

Abstract: This paper is about Lions' open problem on density patches [31]: whether inhomogeneous incompressible Navier-Stokes equations preserve the initial regularity of the free boundary given by density patches. Using classical Sobolev spaces for the velocity, we first establish the propagation of C 1+γ regularity with 0 < γ < 1 in the case of positive density. Furthermore, we go beyond to show the persistence of a geometrical quantity such as the curvature. In addition, we obtain a proof for C 2+γ regularity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…The main issue is to establish that the smoothness of D 0 is preserved through the time evolution (see [10,13,21,22]).…”
Section: Introductionmentioning
confidence: 99%
“…The main issue is to establish that the smoothness of D 0 is preserved through the time evolution (see [10,13,21,22]).…”
Section: Introductionmentioning
confidence: 99%
“…When one assumes that the viscous coefficient is a positive constant, Liao and the second author [20,21] solved the case when the system (1.1) is supplemented with the initial density, ρ 0 (x) = η 1 1 Ω 0 + η 2 1 Ω c 0 , for some pair of positive constants (η 1 , η 2 ), and for any bounded, simply connected domain Ω 0 with W k+2,p (R 2 ) (p ∈]2, 4[) boundary regularity. Danchin and Zhang [12] and Gancedo and Garcia-Juarez [15] proved the propagation of C k+γ regularity of the interface for k = 1 or k = 2. Lately Danchin and Mucha [11] proved the propagation of C 1+γ regularity of density patch which allows vacuum.…”
Section: Introductionmentioning
confidence: 99%
“…Acknowledgment. After this paper was finished, we found that there are several papers on the propagation of C kC regularity of the density patches for viscous inhomogeneous incompressible fluid flow (see [16,18]).…”
mentioning
confidence: 99%